Development and Validation of a Survey to Evaluate Mental Health Knowledge: The Case of Indonesian Pregnant Women - Kusumawati, Yuli; Widyawati, Widyawati; Dewi, Fatwa Sari Tetra (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Internationally, many instruments have been designed to evaluate mental health knowledge; however, in pregnant women is very limited. AIM: Therefore, this study aimed to develop and validate a survey to measure the mental health knowledge of pregnant women. METHODS: In this cross-sectional study, 13 midwives attended the FGD and 10 pregnant women were invited for in-depth interviews to develop an item pool. The content validity was carried out by a panel of 6 experts. The face validity was performed with 5 pregnant women. Next, the construct validity test involved 150 pregnant women who were selected by stratified sampling from 13 public health centers in Surakarta, Indonesia. Analyses were conducted to check content validity, face validity, construct validity, internal consistency reliability, difficulty index, and exploratory factor analysis. RESULTS: A final 20-item Mental Health Knowledge Scale (MHKS) has a content validity index of 0.97 and a correlation value per item greater than the r-table (i.e., 0.1603). In addition, the MHKS has a Kuder–Richardson 20 reliability coefficient of 0.717. Furthermore, the difficulty index ranged from 0.39 to 0.82 which was considered in the good and acceptable category. Construct validity was confirmed using exploratory factor analysis KMO = 0.713, Bartlett’s test p < 0.001. CONCLUSION: Based on the findings, the final version of the MHKS was considered a valid and reliable tool. The instrument can be applied to measure the understanding of pregnant women about pregnancy depression. Further studies require adjustment items to other participants regarding mental health knowledge.